Pollen development and orbicule and pollen grain morphology in species of cephalanthus (rubiaceae-naucleeae) from the Americas - Romero, María Florencia (2017)
Fil: Salas, Roberto. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.